Historical cropland of the continental U.S. from 1850 to 2016, links to GeoTIFFs - Zhen Yu; Chaoqun Lu (PANGAEA, 2017)
We reconstructed the cropland density maps by harmonizing multiple sources of inventory data and high-resolution satellite images. The time-series gridded data depicts the distribution and percentage of cultivated land each year (excluding summer idle/fallow, cropland pasture). The reconstructed annual cropland percentage maps were at 1 km exttimes 1 km resolution covering the conterminous U.S. spanning from 1850 to 2016.
Supplement to: Yu, Z; Lu, C (2018): Historical cropland expansion and abandonment in the continental U.S. during 1850 to 2016. Global Ecology and Biogeography, 27(3), 322-333, https://doi.org/10.1111/geb.12697